An α-diiminato germylene family: syntheses, structures, and reactivity towards C–C coupled digermylene and digermylene oxide. Issue 22 (18th May 2022) - Liu, Jingjing; Shang, Jianxuan; Wei, Jing; Gao, Fangfang; Hou, Lei; Zeng, Fanlong; Li, Anyang; Wang, Wenyuan
Abstract : The synthesis and reactivity of a germylene chloride 2 stabilized by a rigid α-diiminate ligand was systematically explored to afford a new family of germylenes, which bonding nature was revealed by their XRD structures and DFT calculations. Abstract : The synthesis and reactivity of a rigid α-diiminate ligand supported chlorogermylene 2 were demonstrated. The reaction of 2 with hydride donor K[BH( s Bu)3 ] yielded a hydride addition product, a five-membered 6π-aromatic germylene 3 . A nonaromatic germylene 4 was produced by dehydrochlorination of 2 with KN(Si t BuMe2 )2 . Halide abstraction with AlCl3 from 2 afforded a cationic germylene 5, and the reduction of 2 with potassium led to a C–C coupled digermylene 6 via a radical coupling pathway. Hydrolysis of 2 in the presence of NHC (( t Bu-NCH)2 C:) gave digermylene oxide 7 . DFT investigations of central Ge II -rings in molecules 3–5 provided the details of frontier molecular orbitals. The energy level of the lone pair on the Ge atom in 3 is slightly higher than that in 4, indicating that 3 is the stronger σ-donor than 4 . Digermylene 6 and its diastereoisomer 6a feature trans -bent and gauche -bent configurations along their axially chiral C–C bonds, respectively. The conformational and cis–trans isomerism was observed by the isolation of crystal structures 7 and 7a because of intramolecular steric hindrance.